SLC44A2 Frequency, a New TaqMan Real-Time Polymerase Chain Reaction Method for HNA-3A/3B Genotyping, and a New Application of Droplet Digital PCR - Wang, Yufeng; Chen, Xihui; Chen, Qi; Chen, Tangdong; Chen, Kun; Wu, Yuanming; Wang, Li (Frontiers in Genetics, 2022)
Background: Human neutrophil antigen-3A (HNA-3A) and human neutrophil antigen-3B (HNA-3B) are generated by a single-nucleotide polymorphism (rs2288904, c.461G>A) in exon 7 of the choline transporter-like protein-2 gene (CTL2, also known as SLC44A2). Antibodies to HNA-3 can be generated following blood transfusion or other factors resulting in exposure to HNA-3 antigens. These antibodies can cause transfusion-related acute lung injury (TRALI) or neonatal alloimmune neutropenia (NAIN). This study describes a sensitive and specific TaqMan real-time polymerase chain reaction (PCR) method to screen for the HNA-3 genotype using specific primers and probes designed to detect allelic polymorphisms. Considering the high sensitivity and accuracy of droplet digital PCR (ddPCR) in the identification of the rare SLC44A2*2 allele, we used this technique to identify blood donors with the rare HNA-3B antigen and calculate the allele frequency of SLC44A2 in mixed populations with different proportions. Methods: DNA samples purified from 208 donors in northwest China were subjected to TaqMan real-time PCR to detect allelic polymorphisms in SLC44A2. The results were confirmed by Sanger sequencing. The rare HNA-3B antigen was detected by ddPCR. SLC44A2 frequency was determined by two-channel ddPCR. Results: The genotypes of all DNA samples were detected by the TaqMan real-time PCR using specific probes for HNA-3, and the results were consistent with the Sanger sequencing results in respect to the HNA-3A and HNA-3B polymorphisms. The allele frequencies of SLC44A2*1 and SLC44A2*2 in the 208 donors in northwest China were 64.9% (95% confidence interval [CI], 59% to 70.8%) and 35.1% (95% CI, 29.2% to 41%), respectively. The ratio of SLC44A2*2 alleles was accurately detected in all blood pools by ddPCR but not by TaqMan real-time PCR. This allowed for the SLC44A2 frequency in the population to be accurately inferred. Conclusion: This new method of detecting SLC44A2 alleles was highly sensitive and specific, as confirmed by Sanger sequencing. ddPCR using the designed probes resulted in successful detection of the rare HNA-3B antigen. Furthermore, we successfully detected the rare HNA-3B antigen and inferred the SLC44A2 frequency by ddPCR using the probes that we designed.